ANALISIS FAKTOR-FAKTOR MEMPENGARUHI KEPUASAN KERJA KARYAWAN PADA PT. ASTRA CABANG MEDAN - Purba, Betniar (Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study is to analyze the factors that influence employee job satisfaction at PT Astra Medan Branch. The benefits of research help provide input to the leadership of the company in determining policies for the progress of PT Astra Medan Branch and can be used as reference material in enriching and deepening science. The number of samples was 105 respondents, the types of data used were primary and secondary data, and the method of data collection through questionnaires and documentation, the method of data analysis used factor analysis. The results showed that the KMO Measure of Sampling Adequacy (MSA) figure of 0.825 was above 0.50, with a significance of 0,000, so the variables were worthy of further analysis. Scree plot shows the graph, where from factor 1 to factor 2 (source line component number = 1 to 2), the direction of the line decreases sharply. Then from number 2 to number 6, the direction of the line is still decreasing with slope getting smaller. The seventh to twenty-first factors are below the number of the Y axis (eigenvalues). This shows that the six factors are best for summarizing the twenty-one factors that influence employee job satisfaction at PT Astra Medan Branch. The dominant factors affecting job satisfaction of employees of PT Astra Medan Branch are incentives or bonuses, work policies and procedures, promotion of positions, intrinsic of work, social security and official vehicles. The most dominant factor influencing employee job satisfaction is incentives or bonuses. Suggestions that are recommended to company leaders should the company increase the amount of incentives or bonuses, pay attention to the establishment of work policies and procedures, maintain the provision of social security and official vehicles. The company should provide the greatest opportunities for employees with the best performance to be promoted to higher positions.